О возможных вариантах развития укрепленных поселений скифского времени Днепро-Донской лесостепи - Крютченко, А.А. (Археологія і давня історія України, 2020)
На основе материалов раскопок, разведок и данных планиграфии реконструированы этапы развития, а также варианты пространственного изменения городищ скифского времени Днепро-Донской
Лесостепи. Данное исследование позволяет критически отнестись к существующим моделям классификаций и правомерности их применения в ходе
исторических реконструкций. The intensive constructing of fortified settlements
has turned the Dnieper-Don forest-steppe into a huge
building site since the second half of the 6th century
BCE. Mass development of fortifications has begun.
Despite the local features related with topography and
the availability of building materials, it is possible to
distinguish some common vectors.
The hillforts are traditionally perceived by researchers
as static structures that have «frozen» in their original
forms. Recent archaeological researches on the
Tsyrkuny, Bilsk and Mokhnach hillforts in the Forest-
Steppe, confirmed by the series of planographic observations
on the other sites, allow us to classify some
features of the development of fortified settlements.
On the one hand, hillforts are formed on the basis
of the unfortified settlements. Another part was initially
built as fortification. Simple forms of defensive
structures and poorly saturated cultural layer are the
characteristic features of the fortifications of so-called
«shelter-fortresses». The review of the sources allowed
us to say that these sites are hillforts which, for some
unknown reasons, were not settled down, capturing the
first stage of the existence of fortifications, and their
specific cultural layer cannot be the evidence of their
belonging to certain cultural and economic type.
The series of cross-sections of fortifications indicated
the traces of restructuring and repairing of individual
defensive lines throughout the entire period of their
use. There are examples of expanding the area of the
hillfort due to constructing of the new defensive structure
as an extension of the main line or the creation of
the fortification on the next cape that could be united
by the common rampart. Also are known the examples of the special reduction of the area of hillfort. Similar
situation is observed at the last stage of the Bilsk archaeological
complex. In the Late Scythian period, a new type of monuments
appeared on the territory of the Dnieper-Don Forest-Steppe, fortifications consisting of the acropolis
(central fortified part) and large household yard. The current research allows to critically evaluate
the popular models of classifications and the validity of
their application for historical reconstructions. З другої половини VI ст. до н. е. масштабне будівництво
укріплених поселень перетворили Дніпро-Донський Лісостеп у величезний будівельний
майданчик. Розпочалося масове зведення фортифікацій.
Незважаючи на локальні особливості, пов’язані з
місцевою топографією і наявністю матеріалу, можна
простежити деякі спільні вектори розвитку цих укріплених
поселень. Оборонні споруди традиційно сприймаються дослідниками
як статичні структури, що фактично
заморожені в їх початкових формах. Археологічні
дослідження останніх років на Циркунівському
та Більському укріпленнях в Лісостепу, доповнені
серією планиграфічних спостережень на інших
пам’ятках, дозволяють простежити деякі особливості
розвитку укріплених поселень. Частина укріплень формується на основі раніше
існуючих відкритих поселень. Інші з самого початку
спорудили як укріплені фортеці. Перегляд даних
про «городища-сховища» дозволяє сказати, що ці
пам’ятники з невідомих причин не використовувалися.
Вони немов відкарбували на собі перший етап
існування укріплень, а їх слабкий культурний шар
не може бути свідченням їх належності до певного
культурно-господарчого типу. Низка фортифікаційні розрізів вказує на сліди
реконструкції та ремонту окремих оборонних ліній
протягом всього часу їх вжитку. Дані про такі зміни,
поєднані з матеріалами розкопок житлових майданчиків,
дають нам можливість надати приклади розширення
площі фортифікацій, додавши нову лінію
оборони як продовження споруди або створення її
на сусідньому мисі. Останній, ймовірно, міг бути
об’єднаний на пізніх етапах спільним валом. Існують
також приклади навмисного зменшення площі
фортифікацій. Подібна ситуація простежена на
останньому етапі існування Більської фортеці. На
пізньому етапі з’явився новий вид пам’яток — укріплення,
що складаються з акрополя і великого побутового
двору. Це дослідження дає можливість надалі бути
більш критичними при використанні існуючих
моделей класифікації в історичних реконструкціях.